Resonance properties of “bright” plasmons of a finite linear chain of nano-wires made of noble metals - Стогний, Н.П.; Сахненко, Н.К.; Титаренко, А.М. (Radiotekhnika, 2017)
Resonance properties of “bright” localized plasmons of a finite linear chain of nanowires made of noble metals are considered. It is established that in the gap between the nanowires the areas of strong concentration of a field are formed on spatial scales of much smaller length than the wavelength. Position of the increasing concentration area depends on the number of wires in the chain. It is established that with the increase in the number of nanowires and reduction of the gap between them the field concentration increases. It is shown how the change of the properties of the external environment acts on the plasmon resonancethe of wires made of noble metals. The far-field concentration in a narrow wave beam in a chain of silver wires is demonstrated. It was found that with the increase in the number of nanowires in a chain the radiation direction is improving.